Preferowane formy aktywności fizycznej studentów w czasie wolnym w zależności od pory roku = Students` preferred physical activities in leasure time depending on the seasons of the year - Gomołysek, Anna; Łowiński, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The study aimed to answer three research questions. The first question concerned the motifs for which students of both sexes take up physical activity; the second one referred to the preferred forms of activity in relation to the season of the year; and the third question concerned differences between the sexes in relation to choosing recreational forms of physical activity. 451 persons (217 women and 234 men) participated in the study. To conduct the study, the authors used a questionnaire. Its results showed that the seasons of the year have influence on the frequency of taking up physical activity, on its duration, and preferred forms. It also showed that students of both sexes devote too little time to physical activity needed to stay healthy. Differences between both sexes are visible in smoking, the frequency and duration of physical activies, and preferred recreational forms.
Keywords: aktywność fizyczna; studenci; czas wolny; płeć; pory roku; physical activity; students; leisure time; seasons of the year; sex